Mission-critical tasks for assessing risks from vestibular and sensorimotor adaptation during space exploration - Clément, Gilles; Moudy, Sarah C.; Macaulay, Timothy R.; Bishop, Michael O.; Wood, Scott J. (Frontiers in Physiology, 2022)
To properly assess the risk induced by vestibular and sensorimotor adaptation during exploration missions, we examined how long-duration stays on the International Space Station affect functional performance after gravity transitions. Mission-critical tasks that challenge the balance and the locomotion control systems were assessed: i.e., sit-to-stand, recovery-from-fall, tandem-walk, and walk-and-turn. We assessed 19 astronauts, including 7 first-time flyers and 12 experienced flyers, before their flight, a few hours after landing, and then 1 day and 6–11 days later. Results show that adaptation to long-term weightlessness causes deficits in functional performance immediately after landing that can last for up to one week. No differences were observed between first-time and experienced astronaut groups. These data suggest that additional sensorimotor-based countermeasures may be necessary to maintain functional performance at preflight levels when landing on planetary surfaces after a long period in weightlessness.